Mean arterial pressure trajectory with premature cardiovascular disease and all-cause mortality in young adults: the Kailuan prospective cohort study - Song, Zongshuang; Zhao, Haiyan; Wei, Zhihao; Zhao, Wenliu; Tan, Yizhen; Yang, Peng; Chen, Shuohua; Wu, YunTao; Li, Yun; Wu, Shouling (Frontiers in Cardiovascular Medicine, 2023)
The association between mean arterial pressure (MAP) trajectory in young adults and risk of cardiovascular diseases (CVD) and all-cause mortality is not well-characterized. The objective of this study was to investigate the effects of different MAP trajectory on the risk of CVD and allcause mortality among the young.In the Kailuan cohort study, 19171 participants aged 18-40 years were enrolled without CVD (including myocardial infarction, stroke, atrial fibrillation and heart failure). The potential hybrid model was used to fit different trajectory patterns according to longitudinal changes of MAP. Hazard ratios and 95% confidence intervals for risk of CVD and all-cause mortality were analyzed using Cox proportional hazard regression models for participants with different trajectories.Results: Five distinct MAP trajectories were identified during 2006 to 2013. Each of the trajectories was labelled as low-stable, middle-stable, decreasing, increasing, or high-stable. With the low-stable trajectory group as the reference, the multivariate adjusted HR (95%CI) of CVD for the middlestable, decreasing, increasing and high-stable groups were 2.